High commitment work systems and employee well‐being: The roles of workplace friendship and task interdependence - Zhang, Yejun; Sun, Jian‐Min (James); Shaffer, Margaret A.; Lin, Cai‐Hui (Veronica) (Human Resource Management, 2022)
AbstractHuman resource (HR) practices are potent in shaping workplace social relationships, which play a crucial role in employees' well‐being. While the role of formal relationships (i.e., relationships based on prescribed work roles) has received relatively more research attention, little is known about the nexus between HR practices, informal relationships at work and employee well‐being. Drawing on social interdependence theory, we conducted two studies to investigate how high commitment work systems (HCWS) affect employee well‐being through workplace friendship, beyond the effects of formal interpersonal relationships. In Study 1, using time‐lagged data from a sample of 253 full‐time employees, we found that workplace friendship, a type of informal relationship at work, mediated the relationship between HCWS and employee well‐being. In addition, task interdependence strengthened the relationship between HCWS and workplace friendship as well as the indirect effect of HCWS on employee well‐being. In Study 2, we replicated these findings and extended them to multiple forms of well‐being using multilevel data collected at three time points from 310 employees in 61 organizations. Theoretical and practical implications of the findings as well as future research directions are discussed.